METODE VAKT DAN MEDIA PASIR DAPAT MENINGKATKAN KEMAMPUAN MENULIS PERMULAAN BAGI ANAK TUNA GRAHITA SEDANG DI KELAS I SDLB-C YPAC MEDAN - Dasmiati Dasmiati (Universitas Negeri Medan, 2019)
The purpose of this study is to prove that using the VACT Method and Sand media can improve students' abilities in writing the beginning. The research used is Classroom Action Research. The research subjects were 11 students consisting of 5 men and 2 women. The research model was developed by Suharsimi Arikunto. Because in a cycle or round consists of four components, namely: Planning (Planning), Actions (Acting), Observation (Observing), and Reflection (Reflecting). The results of the observation were only two students or (20%) who were able to write the beginning. In the first cycle using the VAKT method and medically the ability increased to 4 students (40%). In cycle II the researcher repeats the beginning of writing the same as the first cycle using the VAKT method and the Sand media, the students 'ability in writing the beginning increases to 7 students (70%) Thus it can be concluded by using the VAKT method and sand media can improve students' ability in write the beginning of B. Indonesia's learning in Medan's 1SDLBC YPAC class. Keywords: VAKT method, mediapasir, write the Beginning.